WHAT DRIVES CAPITAL EXPENDITURE IN INDUSTRIAL REGIONS? EVIDENCE FROM CENTRAL JAVA, INDONESIA - Muhammad Alrayhan Bhagaskara; Ovi Itsnaini Ulynnuha (MESP–FEB UNS, 2026)
This study examines how fiscal capacity influences public investment in industrial-based regions by analyzing the effects of economic growth, Local Own-Source Revenue (PAD), and the General Allocation Fund (DAU) on local government capital expenditure in Central Java during 2018–2024. While fiscal decentralization studies in Indonesia largely focus on transfer dependency and aggregate provincial performance, limited attention has been given to industrial regions where economic expansion may reshape local fiscal dynamics. Using panel data from seven industrial-regional governments, this study addresses that gap. The findings indicate that economic growth, PAD, and DAU exert a positive influence on capital expenditure. The process of industrial expansion has been demonstrated to increase fiscal space and investment incentives. Furthermore, stronger local revenue mobilisation has been shown to enhance fiscal autonomy and development responsiveness. Concurrently, intergovernmental transfers continue to play a pivotal role in fostering regional investment, including in economically vibrant regions. This study makes a contribution to the existing literature on fiscal decentralisation by highlighting a dual fiscal mechanism in industrial regions. The results of the study highlight the necessity of achieving a balance between local revenue strengthening and transfer design in order to ensure the sustainability of productive public investment.